Does Blood Urea Nitrogen Level Predict Severity and High-Risk Endoscopic Lesions in Patients with Nonvariceal Upper Gastrointestinal Bleeding? - Khalid Al-Naamani; Nabil Alzadjali; Alan N Barkun; Carlo A Fallone (Canadian Journal of Gastroenterology)
BACKGROUND: Nonvariceal upper gastrointestinal bleeding (UGIB) is a serious medical condition requiring prompt resuscitation and early endoscopic therapy in those with high-risk endoscopic lesions (HRLs). There are little or no data correlating sole blood urea nitrogen (BUN) level with the severity of nonvariceal UGIB or the presence of HRLs in the adult population.